An Interactive Modeling Method of 3D Model Based on National Cultural Resource Database - Chuan-Ming Suna; Song-Yin Zhengb; Guo-Xin Tanc; Wen-Yuan Zhangd (Guangzhou, 2022)
Aiming at solving the problems of low efficiency and complicated operation of 3D modeling in the process of virtual product development of national culture, this paper discusses a synthesis approach of surface geometry model based on data-driven. Firstly, a shape-based matching algorithm is used to retrieve the corresponding components in the database. Secondly, a new model will be generated through segmenting and assembling these components. Finally, this approach is applied to construct 3D model of scenes and characters in ancient Badong town. The application shows that this approach can generate the geometric model of characters and scenes efficiently and economically in cultural activities.
The 4th Annual International Conference on Information Technology and Applications